2006
DOI: 10.1074/jbc.m608073200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel α-Helix in the First Fibronectin Type III Repeat of the Neural Cell Adhesion Molecule Is Critical for N-Glycan Polysialylation

Abstract: Polysialic acid is a developmentally regulated, anti-adhesive glycan that is added to the neural cell adhesion molecule, NCAM. Polysialylated NCAM is critical for brain development and plays roles in synaptic plasticity, axon guidance, and cell migration. The first fibronectin type III repeat of NCAM, FN1, is necessary for the polysialylation of N-glycans on the adjacent immunoglobulin domain. This repeat cannot be replaced by other fibronectin type III repeats. We solved the crystal structure of human NCAM FN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
55
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 39 publications
(42 reference statements)
6
55
0
Order By: Relevance
“…We solved the crystal structure of NCAM FN1 (40). The structure confirmed the presence of the acidic patch (Asp 506 , Asp 520 , Glu 521 , and Glu 523 ) and also revealed a unique ␣-helix linking strands 4 and 5 of the FN1 ␤-sandwich (40). Replacing the ␣-helix with two threonine residues, as found in the Robo2 FN1 structure, or two alanine residues did not prevent polysialylation.…”
Section: The Neural Cell Adhesion Molecule (Ncam)mentioning
confidence: 77%
See 4 more Smart Citations
“…We solved the crystal structure of NCAM FN1 (40). The structure confirmed the presence of the acidic patch (Asp 506 , Asp 520 , Glu 521 , and Glu 523 ) and also revealed a unique ␣-helix linking strands 4 and 5 of the FN1 ␤-sandwich (40). Replacing the ␣-helix with two threonine residues, as found in the Robo2 FN1 structure, or two alanine residues did not prevent polysialylation.…”
Section: The Neural Cell Adhesion Molecule (Ncam)mentioning
confidence: 77%
“…These results suggested that some or all of the acidic patch residues may be part of a larger polyST recognition region. We solved the crystal structure of NCAM FN1 (40). The structure confirmed the presence of the acidic patch (Asp 506 , Asp 520 , Glu 521 , and Glu 523 ) and also revealed a unique ␣-helix linking strands 4 and 5 of the FN1 ␤-sandwich (40).…”
Section: The Neural Cell Adhesion Molecule (Ncam)mentioning
confidence: 77%
See 3 more Smart Citations